Inducing the partial thermoremanent magnetization: The study of the domain structure and the hysteresis properties of the Fe-Ti bearing minerals in basalts from southern Slovakia, West Carpathian Mts. - ORLICKÝ, Oto; FUNAKI, Minoru (Contributions to Geophysics and Geodesy, 2008)
The basalts of the Pleistocene to Quaternary age were investigated. The partial thermoremanent magnetization (PTRM) in original and artificially prepared samples was induced in the geomagnetic field of the intensity H ≈ 48 mu μT. The domain structure and the hysteresis properties of some selected samples were studied as well. The basalts from 87% of investigated localities have shown the reversed, or partly reversed remanent magnetization (RM). One group of these types of basalts contains dominant, or only small portion of Ti-rich titanomagnetites (Ti-Mt-es), altogether with the titanomaghemite (Ti-Mgh) phase. The second large group of basalts contains dominantly the Ti-Mgh-es, the Ti-Mt-es and more oxidized derivates are in minor portion. They are exclusively of the reversed RM, probably of the self-reversed origin. In the two artificial basalt samples with the Ti-rich Ti-Mt-es and Ti-Mgh phase, a reproducible self-reversal PTRM was induced in the positive geomagnetic field. Many other artificial samples have shown a strong tendency for the acquisition of the self-reversed PTRM. The source of the self-reversed PTRM in these basalts is supposed to be the secondary magnetic phase of the titano-maghemite composition, which has shown a behaviour of small magnetic particles. The basalts with the normal polarity of RM contain dominantly a highly oxidized phase, close to magnetite with hematite in composition, but also the ilmenite is present in these basalts, according to microscopical and Bittern Pattern (BP) observations. From Šomoška locality, the basalts contain also the Ti-rich Ti-Mt-es, but the normal RM is linked to the more oxidized Fe-Ti phase. These types of basalts acquired only normal polarity of PTRM. In the Ti-rich Ti-Mt bearing basalts the domain structures are developed mostly in the rock samples which contain high-temperature oxidized Fe-Ti phases, except for an original low Curie temperature phase.